2017
DOI: 10.1002/tesq.381
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Localized Task‐Based Course in an EFL Context: A Study of Students’ Evolving Perceptions

Abstract: Despite a strong pedagogical orientation, the majority of research examining the effectiveness of task-based language teaching (TBLT) and perceptions toward TBLT has been investigated in isolation rather than embedded in larger curricular contexts (McDonough, 2015). The current study examines the process of developing a TBLT curriculum in South Korea and evolving perceptions toward this particular semester-long task-based course of students from one intact university class. Dynamic systems theory is used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Theories of motivation, like Flow Theory, have begun to garner L2 researchers' attention and results from empirical studies show that language learning activities interact differentially with flow experiences (e.g., Aubrey, 2016Aubrey, , 2017Cho, 2018;Czimmermann & Piniel, 2016;Egbert, 2003;Oxford, 2017;Kirchhoff, 2011;Zuniga & Rueb, 2018). Within the field of task-based language teaching (TBLT), research has examined learners' perception toward several task variables, namely, task modality (Cho, 2018), task complexity (Kim, Jung & Tracy-Ventura, 2017), task types (Bao & Kirkebaek, 2013;Payant, 2019), and task difficulty (Un-udom & Patanasorn, 2020). Task repetition, introduced by Bygate (1996Bygate ( , 2001, has received some attention as of late (see e.g., Bygate, 2018) and has generally shown that repeating a task (or an aspect of a task) benefits learners' language output.…”
Section: In Flow With Task Repetition During Collaborative Oral and Writing Tasksmentioning
confidence: 99%
“…Theories of motivation, like Flow Theory, have begun to garner L2 researchers' attention and results from empirical studies show that language learning activities interact differentially with flow experiences (e.g., Aubrey, 2016Aubrey, , 2017Cho, 2018;Czimmermann & Piniel, 2016;Egbert, 2003;Oxford, 2017;Kirchhoff, 2011;Zuniga & Rueb, 2018). Within the field of task-based language teaching (TBLT), research has examined learners' perception toward several task variables, namely, task modality (Cho, 2018), task complexity (Kim, Jung & Tracy-Ventura, 2017), task types (Bao & Kirkebaek, 2013;Payant, 2019), and task difficulty (Un-udom & Patanasorn, 2020). Task repetition, introduced by Bygate (1996Bygate ( , 2001, has received some attention as of late (see e.g., Bygate, 2018) and has generally shown that repeating a task (or an aspect of a task) benefits learners' language output.…”
Section: In Flow With Task Repetition During Collaborative Oral and Writing Tasksmentioning
confidence: 99%
“…Kim used a combination of two longitudinal data sources to examine students' views on the development of a new task-based language teaching curriculum and quantitatively and qualitatively analyzed the task unit survey of project portfolio entries from 27 Korean EFL learners. Research shows that students' understanding of TBLT changes over time, and multiple factors affect learners' perception of task-based teaching [7]. Farahani uses the theory of complex dynamic systems as a framework to study the dynamic interaction of writing complexity, accuracy, and fluency in second language learning [8].…”
Section: Related Research At Home and Abroadmentioning
confidence: 99%
“…Some studies discuss the benefits of implementing a TBLT approach in smallscale and local studies (e.g. Kim et al, 2017), whereas others examine the introduction of TBLT in larger-scale projects (Markee, 2007;Van den Branden, 2006). Introducing a TBLT approach to L2 teaching, the Belgian education authority developed a large-scale initiative to enhance the quality of L2 teaching and learning in primary and secondary schools more than 15 years ago.…”
Section: Task-based Language Teachingmentioning
confidence: 99%